Neuroprotection after hemorrhagic stroke depends on cerebral heme oxygenase-1 - Kaiser, Sandra; Frase, Sibylle; Selzner, Lisa; Lieberum, Judith Lisa; Wollborn, Jakob; Niesen, Wolf Dirk; Foit, Niels Alexander; Heiland, Dieter Henrik; Schallner, Nils (Antioxidants, 2019)
(1) Background: A detailed understanding of the pathophysiology of hemorrhagic stroke is still missing. We hypothesized that expression of heme oxygenase-1 (HO-1) in microglia functions as a protective signaling pathway. (2) Methods: Hippocampal HT22 neuronal cells were exposed to heme-containing blood components and cell death was determined. We evaluated HO-1-induction and cytokine release by wildtype compared to tissue-specific HO-1-deficient (LyzM-Cre.Hmox1fl/fl) primary microglia (PMG). In a study involving 46 patients with subarachnoid hemorrhage (SAH), relative HO-1 mRNA level in the cerebrospinal fluid were correlated with hematoma size and functional outcome. (3) Results: Neuronal cell death was induced by exposure to whole blood and hemoglobin. HO-1 was induced in microglia following blood exposure. Neuronal cells were protected from cell death by microglia cell medium conditioned with blood. This was associated with a HO-1-dependent increase in monocyte chemotactic protein-1 (MCP-1) production. HO-1 mRNA level in the cerebrospinal fluid of SAH-patients correlated positively with hematoma size. High HO-1 mRNA level in relation to hematoma size were associated with improved functional outcome at hospital discharge. (4) Conclusions: Microglial HO-1 induction with endogenous CO production functions as a crucial signaling pathway in blood-induced inflammation, determining microglial MCP-1 production and the extent of neuronal cell death. These results give further insight into the pathophysiology of neuronal damage after SAH and the function of HO-1 in humans.
CRIS-Team Scopus Importer:2024-03-07
Keywords: Cerebrovascular stroke; Heme oxygenase; Microglia; Neuroprotection; Subarachnoid hemorrhage